The Architecture of Resonance: Decoding How an Acoustic Cavity Shapes Sound Pressure Levels - Xi, Qiyuan (Transactions on Computer Science and Intelligent Systems Research, 2025)
This study investigates the acoustic performance of microspeakers across various cavity configurations using coupled electromagnetic-mechanical-acoustic (E-M-A) simulations and experimental validation. A modular test setup was developed to accommodate interchangeable microspeaker modules with distinct cavity designs, including front-firing, side-firing, and back cavity geometries. The results demonstrate that side-firing cavities induce a distinct Helmholtz resonance peak in the mid-frequency range, while the back cavity contributes additional acoustic compliance, effectively shifting the system’s resonant frequency. Experimental measurements show strong agreement with simulation results, confirming the effectiveness of the coupled E-M-A method for optimizing microspeaker-cavity systems to achieve desired frequency responses.